(untitled) (Global Journal of Science Frontier Research, 2014)
The hydrogen production by water electrolysis consumes electric power (much even). To make this process profitable, we exploited two parameters: the origin of the consumed current and the optimization of the power supply. Indeed, the current is renewable origin (photovoltaic). The connection in parallel of the electrolysers with the photovoltaic module made it possible to increase the production of hydrogen while reducing the electric power consumption. In addition, the use of a voltage regulator made it possible to stabilize the voltage and thus to maintain the hydrogen production on a constant level during all the day.